BCL2A1 is a Potential Biomarker for Postoperative Seizure Control in Patients with Low‐grade Gliomas - You, Gan (CNS Neurosci Ther, 2013)
AIMS: To identify molecular genetic factors that influence preoperative seizure occurrence and postoperative seizure control in patients with low‐grade gliomas (LGGs). METHODS: Fifty‐four WHO grade II astrocytomas were used for microarray analysis under strict inclusion criteria. The primary endpoint was seizure control at 12 months after surgery. Biological processes were investigated by gene ontology (GO) analysis. Quantitative RT‐PCR and immunohistochemistry were used to validate key genes. RESULTS: Differentially expressed genes correlated with seizure occurrence failed to significantly distinguish patients with and without a history of seizures. With respect to postoperative seizure control, a transcript profile of 92 genes was identified, which successfully separated patients with good and poor seizure prognosis. GO analysis revealed that the most striking overrepresentation of genes was found in a category of anti‐apoptotic genes and their regulation. Increased expression was also observed for genes involved in immune and inflammatory responses. BCL2A1 was proven to be a novel marker associated with seizure prognosis. CONCLUSION: Increased anti‐apoptotic activity of tumor cells appears to contribute to seizure recurrence after surgery in patients with LGGs. These findings provide insights that may lead to the development of effective treatment strategies for prolonging the survival of patients with LGG in the future.